Reducing parent-school information gaps and improving education outcomes: Evidence from high-frequency text messages - Samuel G. Berlinski; Matias Busso; Taryn Dinkelman; Claudia Martínez Alvear (Inter-American Development Bank (IDB), 2021)
We conducted an experiment in low-income schools in Chile to test the effects and behavioral changes triggered by a program that sends attendance, grade, and classroom behavior information to parents via weekly and monthly text messages. Our 18-month intervention raised average math GPA by 0.09 of a standard deviation and increased the share of students satisfying attendance requirements for grade promotion by 4.5 percentage points. Treatment effects were larger for students at higher risk of later grade retention and dropout. Leveraging existing school inputs for a light-touch, cost-effective, and scalable information intervention can improve education outcomes in lower-income settings.
Keywords: I25; D8; N36; 330; Education; Information experiment; Parent-School communication; Chile